Forecasting model development for gauge production line of an oilfield service company - Lang, Xiaoling (2014)
Without a short term forecasting system in the gauge production line, the planning is encountering problems in materials requirement planning. Also, a monthly forecasting system is a prerequisite for the production line to reduce the lead time to customer by implementing the Kanban system.